Analysis of the Effect of the Use of a Learning Management System on the Improvement of Human Resource Competence Using the " " Method, Partial Least Squares, and Structural Equation Modeling - Noor Qidam Mujahidin; Bagus Jati Santoso (Journal of Social Research, 2025)
Digital transformation drives companies to continuously develop human resource (HR) competencies to remain relevant and competitive. One of the main challenges is ensuring that technology-based learning systems, such as Learning Management Systems (LMS), are truly effective in supporting employee competency development. This study aims to analyze the impact of the use of the TAMARA LMS at PT IDStar Cipta Teknologi on improving HR competencies and formulate improvement strategies based on the evaluation of the Technology Acceptance Model 2 (TAM2). The approach used is a mixed methods approach, with quantitative analysis using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique, and qualitative analysis through in-depth interviews. The results indicate that Perceived Ease of Use and Attitude Toward Using have a significant effect on Actual Usage, while several external constructs in TAM2, such as Job Relevance and Result Demonstrability, do not show a strong influence on Perceived Usefulness. Qualitative findings support the contribution of LMS to improving soft skills and digital skills, but also highlight challenges such as the lack of regular evaluation, limited content, and minimal managerial support. A synthesis of the two approaches concludes that the TAM2 model remains relevant but needs to be refined to suit the organizational context. This study provides strategic recommendations for optimizing the role of the LMS as an effective and sustainable HR development tool.